A Case Report of Cesarean Scar Pregnancy in the Late First Trimester With an Alive Fetus - Moosavi, Sanaz; Zakariya, Nahideh A.; Alizadeh, Fatemeh Abbas (Current Women's Health Reviews, 2024)
Background: Cesarean scar pregnancy is one of the rare and challenging forms of ectopic pregnancy in treatment. Surgical and medical treatment options are available. Nevertheless, no approach is superior. Case Presentation: The present case reports a 29 years-old lady, presented with 12 weeks and 6 days, cesarean scar pregnancy without any symptoms, with a live fetus that underwent curettage two times. Conclusion: We can use curettage frequently for CSP treatment without methotrexate and, without side effects of other treatments.
Keywords: pregnancy